“MODAL VERBS AND THEIR FUNCTIONS: LEARNING DIFFICULTIES AND SOLUTIONS FOR STUDENTS” (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the English modal verbs (can, could, may, might, must, shall, should, will, would) and their various functions in language use. The study identifies the main difficulties that students face when learning modal verbs, such as understanding multiple meanings of a single verb, using them in context correctly, dealing with their tenseless nature, and applying them with main verbs properly. The research highlights effective teaching strategies to overcome these challenges, including communicative and contextual approaches, interactive exercises, visual aids, and role-playing activities. The findings demonstrate that integrating these methods into the learning process enhances students’ mastery of modal verbs, improves their grammatical competence, and strengthens both written and spoken communication skills. Furthermore, the study suggests that future research can explore technological tools and AI-based methods to further improve the teaching and learning of modal verbs, making the process more efficient and engaging.